A propos de conflits religieux et politiques linguistiques au Cameroun colonial - Bayart, Jean-François (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2010)
Note de lecture à propos de Kenneth J. Orosz, Religious Conflict and the Evolution of Language Policy in German and French Cameroon, 1885-1939, New York, Peter Lang, 2008, XI-346 p., bibliogr., index About Religious Conflicts and Language Policy in Colonial Cameroon Book review of Kenneth J. Orosz, Religious Conflict and the Evolution of Language Policy in German and French Cameroon, 1885-1939, New York, Peter Lang, 2008, XI-346 p., bibliogr., index